RELEVANCE OF THE RAIN IRRIGATION METHOD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
At a time when the countries of the world are experiencing a financial and economic crisis, one of the most important tasks of our state is the rational use of available resources to raise agriculture to a higher level, the introduction of scientifically based, resource-saving, and improved agricultural technologies for the care of agricultural crops, as well as obtaining high and quality yields with minimal costs. Currently, considering the population growth on Earth, the increasing demand for water resources, and the decrease in river water volume year by year, the application of resource-saving irrigation technologies for obtaining high-quality agricultural products is relevant.